Enhancing Self-Confidence Character and Language Skills Through Thematic Discussion In Grade 5 Of Pondok Modern Darussalam Gontor - Luthfi Abdillah Noor Arifin; Fairuz Yudha Alfaridzi; Muhammad Muflih Fathin; Faridj Febrian; Zuhrotul Mufidah (Jurnal Ilmu Pendidikan dan Sosial, 2026)
Character education and official language mastery constitute two fundamental pillars of the curriculum at Pondok Modern Darussalam Gontor (PMDG). This study aims to analyze how the thematic discussion method enhances the self-confidence character and language skills of Grade 5 Kulliyatul Mu'allimin Al-Islamiyah (KMI) students at PMDG. The research employed a descriptive qualitative case study involving Grade 5 KMI students and language instructors as the research participants. Data were collected through participant observation, in-depth interviews, and classroom documentation, then analyzed using the interactive model of data analysis consisting of data reduction, data display, and conclusion drawing with triangulation to ensure credibility. The findings reveal that thematic discussion provides an authentic communicative learning environment that encourages students to express ideas confidently while consistently using Arabic and English as official languages. Students demonstrated noticeable improvements in self-confidence, willingness to participate in discussions, clarity of verbal expression, vocabulary use, and speaking fluency. The integration of thematic content with structured language practice also fostered leadership attitudes, critical thinking, and effective communication. The main contribution of this study lies in demonstrating that thematic discussion functions not only as a language learning strategy but also as an effective character education approach that simultaneously develops self-confidence and communicative competence within an Islamic boarding school context. These findings offer a practical pedagogical model for Islamic educational institutions seeking to integrate character development with foreign language instruction.